The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/pd.4145
|View full text |Cite
|
Sign up to set email alerts
|

Early anatomy ultrasound in women at increased risk of fetal anomalies

Abstract: The high rate of visualization of anatomic structures between 12-17 weeks gestation allows for either early detection of fetal anomalies or parental reassurance in many cases. Subtle anomalies of the heart remain difficult to diagnose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…This increase reflected a gradual change in clinic policy to accept patients with more advanced gestations, more requests for late termination of pregnancy because of fewer options being available elsewhere, and advances in fetal diagnosis. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] More than 95% of patients in this series of 1005 patients had uncomplicated pregnancy terminations with complete evacuation of the uterus The 26 patients presenting with a spontaneous fetal demise late in pregnancy were managed by a D & E procedure following serial multiple laminaria dilation of the cervix. For 12 patients with a single live abnormal fetus, fetal demise was induced at the patient′s request followed by management of the delivery by the patient′s own obstetrician.…”
Section: Resultsmentioning
confidence: 97%
“…This increase reflected a gradual change in clinic policy to accept patients with more advanced gestations, more requests for late termination of pregnancy because of fewer options being available elsewhere, and advances in fetal diagnosis. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] More than 95% of patients in this series of 1005 patients had uncomplicated pregnancy terminations with complete evacuation of the uterus The 26 patients presenting with a spontaneous fetal demise late in pregnancy were managed by a D & E procedure following serial multiple laminaria dilation of the cervix. For 12 patients with a single live abnormal fetus, fetal demise was induced at the patient′s request followed by management of the delivery by the patient′s own obstetrician.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously suggested that the addition of a US examination in early gestation (between 13 weeks and 15 weeks 6 days) may be of the highest benefit in patients with class 3 obesity to improve the rate of completion of anatomic surveys . Many studies have reported US in early gestation for visualizing fetal anatomy in general . However, to our knowledge, no study investigated the role of early US in cardiac screening.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many studies have reported US in early gestation for visualizing fetal anatomy in general. [17][18][19][20] However, to our knowledge, no study investigated the role of early US in cardiac screening.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although the transabdominal approach is most frequently used in routine screening, complementing it with a transvaginal scan is often useful in early pregnancy. Indeed, even though transvaginal probes cannot be manipulated with as many freedom as transabdominal probes, they are closer to the fetus and have better resolution, 7,8 thereby allowing a more detailed evaluation in cases of suspected anomalies.…”
Section: Introductionmentioning
confidence: 99%